Study of the performance of Rh/La2O3eSiO2 and Rh/CeO2 catalysts for SR of ethanol in a conventional fixed-bed reactor and a membrane reactor - da Silva, Adriana M. (2015)
The performance of Rh/La2O3–SiO2 and Rh/CeO2 catalysts for steam reforming of ethanol was investigated in a conventional fixed-bed reactor and a membrane reactor. This reactor was built with a self-supported Pd–Ag membrane, and its performance was compared to that the conventional reactor employing the same residence time and temperature. The effect of steam to ethanol molar ratio, ethanol concentration, temperature and contact time over hydrogen permeation and hydrogen recovery was investigated. In all cases, the ethanol conversion was kept at 100%, and the products formed were only H2, CO2, CO and CH4. In the membrane reactor, the overall ethanol reforming reaction was favored without the formation of carbon deposits. The highest permeated and H2 recovery was obtained for low ethanol content in the feed (high H2O/Ethanol ratio) and the methane formation was unfavored, in agreement with the high production of hydrogen. A slight difference in the hydrogen permeated/feed ethanol ratio was observed at higher sweep gas flow rates being higher for Rh supported on CeO2 in comparison with the Rh/La2O3–SiO2 catalyst. The best results were obtained with a H2O/Ethanol molar ratio equal to 10 and the highest membrane permeation area. Under these conditions, the H2 recovery reached values of about 70% and the hydrogen produced for each mole of ethanol exhibited the highest value close to 2.8.